Effect of combined deep-breathing relaxation and expressive writing therapy on anxiety among students - Wynda Damayanti; Lailatul Fadilah; Osep Yasier Almunsiri; Cucuk Kunang Sari (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Anxiety is an emotional condition resulting from anticipation of an unclear threat, which can affect the learning process and adolescent development if not properly managed. Deep breathing relaxation and expressive writing therapy are complementary therapies that can help reduce stress responses and assist individuals in managing emotions and thoughts related to anxiety. Purpose: To find out the effect of the combination of deep breathing relaxation and expressive writing therapy on anxiety in students. Method: This research design uses a quasi-experimental approach with a one-group pre-test and post-test design. The research sample was taken using a nonprobability sampling technique, namely accidental sampling, with a total of 20 respondents. The research instrument used a questionnaire on the level of adolescent anxiety, which had been adapted and modified by Ways Alqorny in 2023. Results: Based on the results of the Paired T Test on the samples, a p-value of 0.001 was obtained, which is less than the significance value (α = 0.05). Conclusion: The results of this study indicate that there is an effect of the combination of deep breathing relaxation and expressive writing therapy on reducing anxiety in students. Keywords: Adolescents; Anxiety; Deep Breathing Relaxation; Expressive Writing Therapy.